2022
DOI: 10.4049/jimmunol.2100555
|View full text |Cite
|
Sign up to set email alerts
|

The Extracellular ATP Receptor P2RX7 Imprints a Promemory Transcriptional Signature in Effector CD8+ T Cells

Abstract: Development of CD8+ central memory T (Tcm) and resident memory T (Trm) cells, which promote immunity in the circulation and in barrier tissues, respectively, is not completely understood. Tcm and Trm cells may arise from common precursors; however, their fate-inducing signals are elusive. We found that virus-specific effector CD8+ T cells display heterogeneous expression of the extracellular ATP sensor P2RX7. P2RX7-high expression is confined, at peak effector phase, to CD62L+ memory precursors, which preferen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 65 publications
0
23
0
Order By: Relevance
“…This makes it hard to imagine how this receptor could control CD8 + T cells toward effector or memory fates. Among effector CD8 + T cells, a portion of those were found to express high P2RX7 levels as early as 4 days after lymphocytic choriomeningitis virus (LCMV) infection, and these cells are marked for memory development [ 34 ] . As a logical consequence, P2RX7-deficient CD8 + T cells significantly fail to develop into long-lived memory populations [ 28 , 35 ] .…”
Section: Metabolic Control Of T Cells Through Eatp Receptorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it hard to imagine how this receptor could control CD8 + T cells toward effector or memory fates. Among effector CD8 + T cells, a portion of those were found to express high P2RX7 levels as early as 4 days after lymphocytic choriomeningitis virus (LCMV) infection, and these cells are marked for memory development [ 34 ] . As a logical consequence, P2RX7-deficient CD8 + T cells significantly fail to develop into long-lived memory populations [ 28 , 35 ] .…”
Section: Metabolic Control Of T Cells Through Eatp Receptorsmentioning
confidence: 99%
“…If divided based on migratory characteristics, memory CD8 + T cells can be roughly divided into four major subsets: central memory (T CM ), effector memory (T EM ), long-lived effector cells, and resident memory (T RM ). T CM and T RM cells express higher levels of P2RX7, and ablation of this receptor preferentially affects these subsets [ 28 , 34 , 35 ] . We recently found that P2RX7 promotes mitochondrial homeostasis and respiration in nascent memory CD8 + T cells [ 28 ] , which is in turn regulated, at least partially, by P2RX7 inducing the adenosine monophosphate (AMP)-activated protein kinase (AMPK) pathway [ 28 ] and enhanced sensitivity to environmental transforming growth factor-beta (TGF-β) [ 34 , 35 ] .…”
Section: Metabolic Control Of T Cells Through Eatp Receptorsmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 21, 2023. ; https://doi.org/10.1101/2023.04. 19.537580 doi: bioRxiv preprint antigen-specific CD8 + T cells 34,35,36 and is crucial for the generation and survival of memory CD8 + T cells 32,34,37 . In addition to Panx1 export, eATP can accumulate through infectioninduced tissue damage 38 .…”
mentioning
confidence: 99%
“… 7 In line with this observation, recent work has demonstrated that P2X7R expression is critical for memory CD8 T cell differentiation and that P2X7R high CD8 T cells preferentially generate long-lived central memory T cells (T CM ) and T RM populations, important subsets for tumor immune surveillance that have been shown to be susceptible to NICD. 3 , 8 Interestingly, P2X7R is also expressed in antigen-presenting dendritic cells (DC) where its activation leads to increased production of interleukin (IL)-18 in a NOD-, LRR- and pyrin domain-containing protein 3 (NLRP3)-dependent manner, in turn activating other immune cells to produce interferon-γ (IFN-γ) and increase tumor immunogenicity. 9 Treatment of lung and melanoma tumor-bearing mice with a P2X7R activator potentiated the anti-tumor effect of anti-PD-1 antibody, with combined treatment leading to tumor regression and memory antitumor immune responses.…”
mentioning
confidence: 99%
“…P2X7R + CD8 T cells and DCs appear to be critical for generating immune responses and tumor memory. 8 , 9 In a subset of patients with ART1 high tumors, P2X7R + anti-tumor memory T cell progenitors as well as DCs may be depleted through NICD, thus abrogating, at both the priming and effector level, the ability of the patient to mount effective immune responses against their cancer. This tumor defense mechanism is likely particularly engaged at times of ongoing cellular stress or cell death when NAD + is released in the TME to serve as a substrate for ART1.…”
mentioning
confidence: 99%